Good governance, the informal sector and protection of competition in the market : lessons from CARICOM - Stewart, Taimoon (2004)
States that an examination of competition issues in selected CARICOM countries revealed that, even if there were competition law and effective enforcement in these economies, this would have been insufficient to protect the process of competition in the market. Sees the need to address issues of good governance simultaneously with introducing and implementing a competitive regime.